2017
DOI: 10.1049/el.2017.1282
|View full text |Cite
|
Sign up to set email alerts
|

Low cross‐polarisation high‐isolation frequency scanning aperture coupled microstrip patch antenna array with matched dual‐polarisation radiation patterns

Abstract: A method of beam matching between two linear polarised radiation patterns of a dual-polarised frequency scanning antenna is proposed, implemented, and tested. A meticulous phase match process between the outputs of both individual cells and the whole corresponding horizontal and vertical feed lines is carried out. To verify the simulation results and to take the coupling effect into account, the radiation patterns of an isolated column, as well as those of three columns, are measured. In agreement with the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, ρ hv is low and not up to expectations due to the antenna beam mismatch and other system instability issues. The beam mismatch is being addressed by a redesign of the frequency-scan dual-polarization column antennas (Saeidi-Manesh et al, 2017). The CPPAR electronics is also being redesigned and rebuilt to have a stable system so that many CPPAR related issues such as commutating scan, sector-to-sector isolation, surface wave effects, and accurate weather measurements can be addressed/demonstrated.…”
Section: Polarimetric Par Technologymentioning
confidence: 99%
“…However, ρ hv is low and not up to expectations due to the antenna beam mismatch and other system instability issues. The beam mismatch is being addressed by a redesign of the frequency-scan dual-polarization column antennas (Saeidi-Manesh et al, 2017). The CPPAR electronics is also being redesigned and rebuilt to have a stable system so that many CPPAR related issues such as commutating scan, sector-to-sector isolation, surface wave effects, and accurate weather measurements can be addressed/demonstrated.…”
Section: Polarimetric Par Technologymentioning
confidence: 99%
“…Based on weather radar requirements and deficiencies of the planar array antenna, a cylindrical polarimetric phased‐array antenna is designed and proposed for MPAR application. The CPPAR demonstrator, a 2 m diameter cylindrical array antenna designed and fabricated by the Advanced Radar Research Center (ARRC) of the University of Oklahoma (Saeidi‐Manesh et al, ), is shown in Figure a. As shown in Figure b M × N element cylindrical array antenna consists of N rows of M‐element circular array antenna.…”
Section: Planar or Cylindrical Geometry?mentioning
confidence: 99%
“…Taking advantages of PDMs, the effective bandwidth can be doubled [1]. However, PDM requires strict cross-polarisation discrimination (XPD) of the adopted orthogonally polarised antenna [2][3][4][5]. Recently, satellite communications on the move (SOTMs) are undergoing rapid advancement.…”
Section: Introductionmentioning
confidence: 99%